Vaccination as a social practice: towards a definition of personal, community, population, and organizational vaccine literacy - Chiara Lorini; Marco Del Riccio; Patrizio Zanobini; Roberto Luigi Biasio; Paolo Bonanni; Duccio Giorgetti; Valerio Allodola Ferro; Andrea Guazzini; Olfa Maghrebi; Vieri Lastrucci; Lisa Rigon; Orkan Okan; et al. (BMC Public Health, 2023)
Abstract Background A comprehensive and agreed-upon definition of vaccine literacy (VL) could support the understanding of vaccination and help policy-makers and individuals make informed decisions about vaccines. Methods To shed some light on this debate and provide clarity, a scoping review was conducted to collect, summarize, and analyse available definitions of VL. Based on the findings of the scoping review, a new and comprehensive definition was proposed by a panel of experts. Results Fifty-three articles were included, and two of them appeared to be the milestones around which the other definitions were grouped. The new definition proposed by the panel of experts included not only the personal perspective, but also the community, population, and organizational perspectives. Moreover, due to the increasing complexity of the social context with respect to the ability to navigate, understand, and use information and services, the definition of organizational vaccine literacy and the attributes of a vaccine literate healthcare organization have been proposed. Conclusion The new definition can contribute to the overall paradigm of health literacy and its distinct component of vaccine literacy, possibly improving the implementation of public health strategies to allow vaccination to be understood as a social practice by the entire community. This study describes the conceptual foundations, the competencies, and the civic orientation to be considered when developing measurement tools devoted to assessing VL at the different levels and in different contexts.